Pengaruh Konsentrasi Sorbitol terhadap Karakteristik Edible Film Pati Kentang (Solanum tuberosum L.) dan Pengaplikasiannya pada Dodol Nanas - RIZKY RAMDHANI; VINA AMALIA; ASSYIFA JUNITASARI (UIN Sunan Gunung Djati Bandung, 2022)
Plastic packaging on food has a negative impact on the environment because it is non-biodegradable. One way that can be done to overcome this problem is to replace plastic packaging on non-biodegradable food with biodegradable plastic, so that edible films are developed. An example of a material that can be used in the manufacture of edible films is potato starch. Edible films made of polysaccharides have low mechanical properties, so it is necessary to add a material that can improve the mechanical properties, namely plasticizer. The addition of sorbitol as a plasticizer is expected to improve the mechanical properties caused. In this study, the manufacture of edible films began with the extraction of potato starch, then added with sorbitol plasticizer with a concentration variation of 0.6; 0.9; and 1.2% (v/v). The edible film formed was then characterized by testing its physical and mechanical properties. Then applied as pineapple lunkhead packaging and hedonic organoleptic tests and descriptions were carried out. The addition of variations in the concentration of sorbitol affects the physical and mechanical properties caused. The morphology of the edible film was shown by SEM to determine the homogeneity of the mixture between starch and plasticizer. The best treatment in this study was edible film with the addition of 0.9% (v/v) sorbitol variation with a thickness of 0.0922 mm, tensile strength 9.84 MPa, elongation 16%, Young's modulus 0.615 MPa, and water uptake 111.39 %. The resulting edible film has a good level of homogeneity and a smooth surface. Application of edible film from potato starch as packaging on pineapple lunkhead can be accepted as an alternative packaging material for food based on organoleptic tests